Stress response in tomato as influenced by repeated waterlogging - Umićević, Sonja; Kukavica, Biljana; Maksimović, Ivana; Gašić, Uroš; Milutinović, Milica; Antić, Marina; Mišić, Danijela (Frontiers in Plant Science, 2024)
The aim of this study was to evaluate tomato genotypes for their sensitivity to waterlogging stress applied during early vegetative growth and at full flowering stage, analyzing profiles of phenolic compounds, the activity of class III peroxidase (POX), hydrogen peroxide (H2O2) and malondialdehyde (MDA) content. In addition, we assessed the impact of repeated waterlogging treatment (also called priming) on the tomato tolerance to oxygen deficiency. Content of oxidative parameters (H2O2 and MDA) exhibited an increase in leaves of tomato plants that underwent waterlogging stress compared to control plants. Moreover, oxidative parameters showed positive correlation with proteins and phenolics content. The obtained correlations can indicate that one of the response strategies of tomato plants to waterlogging is the increased synthesis of proteins and phenolic compounds. A positive correlation was shown between POX activity and the content of phenolic compounds, indicating their independent roles in the removal of ROS. Changes in the phenolic profiles after the exposure of plants to waterlogging stress are recorded, and these changes were more severe in leaves and fruits of GB1129 and NJ genotypes than in GB1126. Thus, genotype GB1126 is the most efficient in maintaining the phenolic profiles of leaves and fruits, and therefore of the nutritive and organoleptic qualities of fruits following the exposure to waterlogging. Also, genotype GB1126 exhibited the ability to maintain the content of oxidative parameters during waterlogging at certain growth stages, implying certain waterlogging tolerance. Waterlogging triggered stress memory but not at all growth stages. The most pronounced stress memory was obtained in fruit samples in the phase of full fruit maturity on the 1st truss. This study shed light on the defense mechanisms of tomato plants to repeated waterlogging stress from the perspectives of the changes in the composition of major phenolics, and pointed to the 5-O-caffeoylquinic acid and rutin as the chemical markers of the waterlogging stress tolerance in tomato. However, it remains to be determined whether this modulation has a positive or negative effect on the overall plant metabolism. Further investigations are needed to fully elucidate the benefits of waterlogging pretreatment in this context.